Identification and expression pattern analysis of the OsSnRK2 gene family in rice - Yu, Tongyuan; Cen, Qiwen; Kang, Lihua; Mou, Wangshu; Zhang, Xiaoqin; Fang, Yunxia; Zhang, Xian; Tian, Quanxiang; Xue, Dawei (Frontiers in Plant Science, 2022)
Sucrose non-fermenting-1-related protein kinase 2 (SnRK2) is a class of plant-specific serine/threonine (Ser/Thr) protein kinase that plays an important role in rice stress tolerance, growth and development. However, systematic bioinformatics and expression pattern analysis have not been reported. In the current study, ten OsSnRK2 genes were identified in the rice genome and located on 7 chromosomes, which can be classified into three subfamilies (I, II, and III). Many cis-regulatory elements were identified in the promoter region of OsSnRK2 genes, including hormone response elements, defense and stress responsive elements, indicating that the OsSnRK2 family may play a crucial role in response to hormonal and abiotic stress. Quantitative tissue analysis showed that OsSnRK2 genes expressed in all tissues of rice, but the expression abundance varied from different tissues and showed varietal variability. In addition, expression pattern of OsSnRK2 were analyzed under abiotic stress (salt, drought, salt and drought) and showed obvious difference in diverse abiotic stress. In general, these results provide useful information for understanding the OsSnRK2 gene family and analyzing its functions in rice in response to ABA, salt and drought stress, especially salt-drought combined stress.